The influence of risk management to credit lending - Agustin, Ewith Dade; Bayunitri, Bunga Indah (Goodwood Publishing, 2020)
Purpose: The purpose of this study was to determine whether risk management influences the provision of credit to PT. BPR Supra Antapersada Bandung. The factors tested in this study were risk management as the independent variable, while credit as the dependent variable. Research Methodology: The method of analysis used is the explanatory method, while the number of samples in this study amounted to 37 employees of PT. BPR Supra Antapersada Bandung. In this study, the analytical method used was a partial (t-test) significance of 5%. The program used to analyze the data was the Version 21.00 of Social Science Statistical Package (SPSS). Results: The research results partially and simultaneously indicate that risk management affects lending to PT. BPR Supra Antapersada Bandung at 68.1%. Limitations: Limitation of the problem is the provision of credit to BPR Supra Antapersada in Bandung. Contribution: This study can be useful for the banking credit sector, and for future researchers. Keywords: Credit lending, Risk management, PT. BPR Supra Antapersada